Different therapeutic regimens in the treatment of metastatic prostate cancer by performing a Bayesian network meta-analysis. (June 2019) - Zhang, Qijie; Cheng, Hong; Wang, Yi; Tian, Ye; Xia, Jiadong; Wang, Yichun; Zhou, Xiang; Meng, Xianghu; Wang, Yamin; Gu, Min; Song, Ninghong
Abstract: Background: Although androgen deprivation therapy with or without chemotherapy are currently the mainstay of therapy for metastatic prostate cancer, accumulating data suggested the survival benefits from definitive local therapy such as radical prostatectomy or radiation therapy. Hence, this network meta-analysis was aimed to provide a hierarchy of different therapeutic regimens for mPCa. Methods: Relevant studies were retrieved comprehensively by searching the online databases of PubMed, EMBASE and Web of Science, published before July 1st, 2018. With the help of R-3.4.0 software and "gemtc-0.8.2" package, network meta-analysis was performed by random-effect model within a Bayesian framework. Hazard ratios and corresponding 95% credible intervals were calculated by Markov chain Monte Carlo methods. The surface under the cumulative ranking curve was also incorporated to rank the corresponding therapeutic regimens. Results: A total of 55, 363 cases from 17 studies were ultimately involved in this study. Ten different therapeutic regimens and three clinical endpoints were finally assessed. As illustrated by our results, local therapy (such as radical prostatectomy or radiation therapy) could provide a relatively more favorable survival rate than systematic therapies (no local therapy, androgen deprivation therapy or androgen deprivation therapy + chemotherapy). Meanwhile, in the comparison of radiation therapy, brachytherapy and intensity modulated radiation therapy were among the best two therapies. Furthermore, radical prostatectomy had a relatively lower cancer specific mortality or all-cause mortality than brachytherapy or intensity modulated radiation therapy, in the comparison of local therapy, whereas brachytherapy showed a relatively longer overall survival than radical prostatectomy. Conclusions: Our results indicated that local therapy was better than no local therapy. In a comprehensive comparison of three clinical endpoints (overall survival, cancer specific mortality or all-cause mortality), radical prostatectomy had a relatively lower cancer specific mortality or all-cause mortality than radiation therapy, whereas brachytherapy was superior to radical prostatectomy for overall survival. Highlights: Comprehensive comparisons of different treatments for metastatic prostate cancer were provided. It was the first time for us to shed light on local treatment showed its superiority than no local therapy. Radical prostatectomy had a relatively lower cancer specific mortality or all-cause mortality than radiation therapy. Brachytherapy was superior to radical prostatectomy for overall survival.